Current challenges in open-source bioimage informatics - Cardona, Albert; Tomancak, Pavel (Nature methods, 2012)
We discuss the advantages and challenges of the open-source strategy in biological image analysis and argue that its full impact will not be realized without better support and recognition of software engineers' contributions to the biological sciences and more support of this development model from funders and institutions.